2021
DOI: 10.1073/pnas.2025540118
|View full text |Cite
|
Sign up to set email alerts
|

Mapping pollution exposure and chemistry during an extreme air quality event (the 2018 Kīlauea eruption) using a low-cost sensor network

Abstract: Extreme air quality episodes represent a major threat to human health worldwide but are highly dynamic and exceedingly challenging to monitor. The 2018 Kīlauea Lower East Rift Zone eruption (May to August 2018) blanketed much of Hawai‘i Island in “vog” (volcanic smog), a mixture of primary volcanic sulfur dioxide (SO2) gas and secondary particulate matter (PM). This episode was captured by several monitoring platforms, including a low-cost sensor (LCS) network consisting of 30 nodes designed and deployed speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Similar to this six-month study, in several of the network nodes Craw-ford et al [2021] found SO 2 sensors to experience technical difficulties over the 17-day deployment period. The results from this combined-sensor low-cost network were successful, with similar PM and SO 2 measurements recorded as the regulatory reference-grade network and at a much higher spatial resolution [Crawford et al 2021]. Crawford et al [2021] do not report on the performance of the network over long-term deployment so it is not possible to make a direct comparison with that of the AQMesh network at Masaya.…”
Section: Alternative Air Quality Monitoring Toolsmentioning
confidence: 70%
See 1 more Smart Citation
“…Similar to this six-month study, in several of the network nodes Craw-ford et al [2021] found SO 2 sensors to experience technical difficulties over the 17-day deployment period. The results from this combined-sensor low-cost network were successful, with similar PM and SO 2 measurements recorded as the regulatory reference-grade network and at a much higher spatial resolution [Crawford et al 2021]. Crawford et al [2021] do not report on the performance of the network over long-term deployment so it is not possible to make a direct comparison with that of the AQMesh network at Masaya.…”
Section: Alternative Air Quality Monitoring Toolsmentioning
confidence: 70%
“…Measurement of volcanic SO 2 at sub-ppmv levels has also been demonstrated using electrochemical sensors [Hagan et al 2018;Roberts et al 2018]. In a recent study, networks of low-cost SO 2 and particle sensors have been used to monitor volcanic pollution from the 2018 eruption of Kīlauea (USA) [Crawford et al 2021].…”
Section: Introductionmentioning
confidence: 99%
“…This issue has received significant attention recently with the introduction of low-cost fixed networks and hand-held, portable sensors that augment higher accuracy but costly regulatory air quality monitoring. These low-cost PM and SO 2 sensors perform reasonably well for monitoring volcanic air pollution in communities, as demonstrated during the Kīlauea 2018 eruption (Whitty et al 2020;Crawford et al 2021) and in Iceland (Gíslason et al 2015). Air quality forecast models can complement ambient air monitoring and now play an important role in informing the public about current and predicted levels of volcanic pollution in some locations (Barsotti 2020;Holland et al 2020).…”
Section: Hazard and Exposure Assessmentmentioning
confidence: 92%
“…Currently, the utility of low-cost sensors is much greater when they are benchmarked against reference-grade instruments, which may not be available, even regionally. Future improvements in sensor accuracy, calibration, and reliable global satellite internet may contribute to better exposure assessment (Kizel et al 2018;Crawford et al 2021).…”
Section: Emerging Themes Knowledge Gaps and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation